TIPOLOGI NILAI-NILAI MOTIVASI PELAYANAN PUBLIK DI PDAM KABUPATEN MAMASA - Oktovianus Oktovianus; Aco Dahrul Saharuddin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to determine the value of the typology of motivation for public services in PDAM Mamasa Regency. Research is carried out systematically, factually and accurately regarding the facts and facts of certain populations. The results show that the typology of the value of public service motivation is commitment to the public interest; empathy; and self-sacrifice of relatively high value. Meanwhile, the value of the importance of public policy making is relatively low compared to other values. The value of interest in public policy making is the lowest proportion. Commitment to the greatest presentation public interest. The second largest percentage value of empathy. The value of self-sacrifice obtained in the third presentation.